2020
DOI: 10.7554/elife.58029
|View full text |Cite
|
Sign up to set email alerts
|

Sox17 and β-catenin co-occupy Wnt-responsive enhancers to govern the endoderm gene regulatory network

Abstract: Lineage specification is governed by gene regulatory networks (GRNs) that integrate the activity of signaling effectors and transcription factors (TFs) on enhancers. Sox17 is a key transcriptional regulator of definitive endoderm development, and yet, its genomic targets remain largely uncharacterized. Here, using genomic approaches and epistasis experiments, we define the Sox17-governed endoderm GRN in Xenopus gastrulae. We show that Sox17 functionally interacts with the canonical Wnt pathway to specify and p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 74 publications
(192 reference statements)
2
25
0
Order By: Relevance
“…Alternatively, through co-occupancy at those sites, SOX-2 could negatively impact on POP-1 activity directly or by sequestering co-factors such as β-catenin. Such model is consistent with studies in vertebrates, where SOX factors have been shown to interact with TCF/β-catenin factors in several ways: at the DNA via interaction with β-catenin and/or TCF, or by impacting β-catenin stability (Akiyama, 2004; Kormish et al, 2010; Mukherjee et al, 2020). The negative interactions between SOX-2 and the Wnt signaling could further be reinforced by CEH-6/POU, as mOct4 has been shown to inhibit Tcf/β-catenin stability and transcriptional activity in mES cells and Xenopus (Cao et al, 2007; Abu-Remaileh et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Alternatively, through co-occupancy at those sites, SOX-2 could negatively impact on POP-1 activity directly or by sequestering co-factors such as β-catenin. Such model is consistent with studies in vertebrates, where SOX factors have been shown to interact with TCF/β-catenin factors in several ways: at the DNA via interaction with β-catenin and/or TCF, or by impacting β-catenin stability (Akiyama, 2004; Kormish et al, 2010; Mukherjee et al, 2020). The negative interactions between SOX-2 and the Wnt signaling could further be reinforced by CEH-6/POU, as mOct4 has been shown to inhibit Tcf/β-catenin stability and transcriptional activity in mES cells and Xenopus (Cao et al, 2007; Abu-Remaileh et al, 2010).…”
Section: Discussionsupporting
confidence: 90%
“…Wnt and SOX interplay and mutual control led to a hypothesis pointing out that interactions between lineage-specific SOX TFs and β-catenin/TCF govern specificity of Wnt/β-catenin dependent transcription ( Mukherjee et al, 2020 ). This idea is supported by the study conducted by Hagey and Muhr (2014) .…”
Section: Sox Interplay With Wnt/β-catenin Signalingmentioning
confidence: 99%
“…Our SOM results suggest that such an interaction may be more wide-spread during Xenopus mesendoderm specification. Additionally, the binding of mesodermal regulator Tbxt (Smith et al, 1991) at stage 12 and the endodermal regulator Sox17 (Hudson et al, 1997; Mukherjee et al, 2020) at stage 10.5 correlated with each other, more so than with the binding of other TFs (Figure S1E, Figure S3). This finding is interesting as Sox17 is generally considered to be an endodermally expressed gene, whereas Tbxt is mesodermally expressed.…”
Section: Resultsmentioning
confidence: 95%
“…Numerous genomic analyses of individual TFs have been used to understand early Xenopus development (Yoon et al, 2011; Gentsch et al, 2013; Chiu et al, 2014; Yasuoka et al, 2014; Nakamura et al, 2016; Kjolby and Harland, 2017; Charney et al, 2017b; Paraiso et al, 2019; Gentsch et al, 2019; Mukherjee et al, 2020; Afouda et al, 2020). In these experiments, combining a single, or a few, ChIP-seq dataset(s) and RNA-seq datasets in wild type and perturbed states have been used to identify direct transcriptional targets of TFs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation